The Loneliness of “Adam”: An Attempt at Symbolic Interpretation - Świeżyński, Adam (Laval théologique et philosophique, 2016)
The experience of loneliness is usually seen as a negative aspect of human existence and something to overcome. However, it is worth trying to break free, if only on a trial basis, from the established traditional perception of loneliness, and strive to reduce it immediately from being one of the main sources of human affliction and to rethink its importance in human life. In order to do this, we must first consider the question of the essence of loneliness (ontology of loneliness), and then examine the question of its axiological status, i.e. its value (axiology of loneliness). The ontological dimension and the axiological dimension of the issue should include the opportunity to construct the concept of human loneliness, by taking into account its internal (phenomenological) and external (essential) aspect. The purpose of this paper is to propose an outline concept of loneliness, which, on the basis of findings on its essence, seeks to determine its axiological nature. The designated point of departure is the biblical image of human loneliness presented in Genesis (Gen. 2:4b-24).